Interleukin-6 receptor specific RNA aptamers for cargo delivery into target cells - Meyer, Cindy (Landes Bioscience, 2012)
Aptamers represent an emerging strategy to deliver cargo molecules, including dyes, drugs, proteins or even genes, into specific target cells. Upon binding to specific cell surface receptors aptamers can be internalized, for example by macropinocytosis or receptor mediated endocytosis. Here we report the in vitro selection and characterization of RNA aptamers with high affinity (K(d) = 20 nM) and specificity for the human IL-6 receptor (IL-6R). Importantly, these aptamers trigger uptake without compromising the interaction of IL-6R with its natural ligands the cytokine IL-6 and glycoprotein 130 (gp130). We further optimized the aptamers to obtain a shortened, only 19-nt RNA oligonucleotide retaining all necessary characteristics for high affinity and selective recognition of IL-6R on cell surfaces. Upon incubation with IL-6R presenting cells this aptamer was rapidly internalized. Importantly, we could use our aptamer, to deliver bulky cargos, exemplified by fluorescently labeled streptavidin, into IL-6R presenting cells, thereby setting the stage for an aptamer-mediated escort of drug molecules to diseased cell populations or tissues.